The Effect of 4D-5D BIM Implementation and Visualization on Improving Product Quality and Timing of Toll Road Infrastructure Projects - Anugrah Putra, Tommy; Suroso, Agus (Green Publisher Indonesia, 2025)
The toll road construction project is inherently complex and prone to delays due to its multi-phase implementation process. In the era of the Industrial Revolution 4.0, the adoption of digital construction technologies is increasingly emphasized to enhance project efficiency and outcomes. One such technology is Building Information Modeling (BIM), which serves as a vital digital asset supporting data integration and informed decision-making throughout the construction lifecycle. This study aims to analyze the influence of BIM implementation on the quality of engineering products and how engineering product quality subsequently affects implementation time performance. Employing a quantitative approach with linear regression analysis, data were collected from toll road construction projects that have adopted BIM practices. The findings reveal a significant influence of BIM implementation on the quality of engineering products by 71.00%, and a further influence of engineering product quality on the performance of implementation time by 77.10%. These results demonstrate that BIM plays a critical role in improving construction quality and accelerating project completion. The study concludes that the structured and integrated nature of BIM enhances engineering output and time efficiency, making it a strategic tool for national infrastructure projects. It is recommended that stakeholders in the construction sector adopt BIM more comprehensively to optimize quality assurance and reduce the risk of project delays